Implementasi Sistem Manajemen Kinerja yang Efektif dan Efisien dalam Organisasi - Nurul Indawati; Fajri Anggy Efendi; Muhammad Alkirom Wildan (MES Management Journal, 2024)
This study examines how crucial it is to combine financial and non-financial performance metrics in order to evaluate an organization's efficacy and efficiency. Profit and revenue are important financial indicators, but they do not give a full picture of performance. Non-financial metrics like customer satisfaction, product quality, and innovation are also essential. Integrating both types of measures offers a more comprehensive view and enables organizations to make better decisions and improve competitiveness. The findings suggest that a holistic approach to performance measurement supports the achievement of long-term goals effectively and sustainably.